Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10916-016-0486-5
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Models of Healthcare Information Systems and Technologies: a Literature Review

Abstract: The maturity models are instruments to facilitate organizational management, including the management of its information systems function. These instruments are used also in hospitals. The objective of this article is to identify and compare the maturity models for management of information systems and technologies (IST) in healthcare. For each maturity model, it is identified the methodology of development and validation, as well as the scope, stages and their characteristics by dimensions or influence factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 19 publications
0
68
0
3
Order By: Relevance
“…For example, Wendler [2] identified 231 articles and provides an overview of the MMs domains, research design, development, and validation. Carvalho et al [46] identified 14 MMs for information systems and technologies (IST) management in healthcare. Tarhan et al [47] (2016) sought an overall understanding of the existence, characteristics, and use of MMs in business process management; in a sample of 61 studies, they identify 20 business process MMs.…”
Section: Phase 1-problem Formulation and Question Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wendler [2] identified 231 articles and provides an overview of the MMs domains, research design, development, and validation. Carvalho et al [46] identified 14 MMs for information systems and technologies (IST) management in healthcare. Tarhan et al [47] (2016) sought an overall understanding of the existence, characteristics, and use of MMs in business process management; in a sample of 61 studies, they identify 20 business process MMs.…”
Section: Phase 1-problem Formulation and Question Identificationmentioning
confidence: 99%
“…The MM scope can be generic (i.e., apply to all organizational processes) or more specific (i.e., apply to a specific process). Carvalho et al [46] use the MMs scope analysis. In the context of healthcare information systems to identify: (i) generic or comprehensive models (i.e., models representing the hospital information system); and (ii) highly specialized models targeting specific process (i.e., electronic medical record process).…”
Section: Phase 1-problem Formulation and Question Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ Sources 4,11,17,31,37,68,80,88] [ Sources 37,71,74,80,85] [ Sources 2,3,17,19,20,36,37,56,59,80] [ Sources 4,12,15,24,26,32,35,37,39,41,42,46,49,54,55,57,61,63,64,71,74,75,76,77,78,79,80,83,86 Figure 7. Sources with respect to the applicability scope/scale of the MMs.…”
Section: Rq 22mentioning
confidence: 99%
“…The designed maturity models vary based on their scope, which determines the degree of the model's application within its domain. The maturity models range from generic ones, which are applied to most organisational processes, to specialised models that are employed to assess a specific process within the firm [49].…”
Section: Maturity Frameworkmentioning
confidence: 99%